2019
DOI: 10.1155/2019/8328490
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammation in the Pathogenesis of Diverticular Disease

Abstract: Diverticulosis of the colon is the most common condition in Western societies and it is the most common anatomic alteration of the human colon. Recurrent abdominal pain is experienced by about 20% of patients with diverticulosis, but the pathophysiologic mechanisms of its occurrence are not completely understood. In the last years, several fine papers have showed clearly the role of low-grade inflammation both in the occurrence of symptoms in people having diverticulosis, both in symptom persistence following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 65 publications
0
17
0
2
Order By: Relevance
“…This behavior is similar to acute diverticulitis, in which the majority of recurrences are recorded during the first 2 years after the first episode of acute diverticulitis [ 20 ]. A possible explanation is that low-grade inflammation may play a role either in SUDD or in acute diverticulitis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…This behavior is similar to acute diverticulitis, in which the majority of recurrences are recorded during the first 2 years after the first episode of acute diverticulitis [ 20 ]. A possible explanation is that low-grade inflammation may play a role either in SUDD or in acute diverticulitis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few pathology papers have described a significant proportion of nonneoplastic urinary bladder diver-ticula having inflammatory changes [ 9 11 ]; however, as these were either postbiopsy or resected samples, it was difficult to determine if such inflammatory changes were directly involved in diverticulum formation or were the result of stasis of urine and the underlying clinical condition leading to the biopsy and resection. Previous papers looking at colonic diver-ticula disease found no signs of inflammatory change in histological samples [ 12 14 ]. While the colon and urinary bladder are different organs with functionally different processes and contents, it would not be wrong to postulate the limited role inflammation has in causing urinary bladder diverticula to form.…”
Section: Discussionmentioning
confidence: 97%
“…However, a randomized clinical trial found no effect of memantine on outcomes related to MS disease severity compared with placebo [ 42 ]. The observed potential benefit of memantine on diverticulosis could be due to its neuroprotective effects, decreasing the neural damage and regeneration that is observed in subjects with diverticular disease [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%